Prevalensi Malaria Asymptomatic Pada Kelompok Penduduk Paling Berisiko Tertular Di Kecamatan Kalipucang Kabupaten Ciamis Jawa Barat - Lukman Hakim (ASPIRATOR - Journal of Vector-borne Disease Studies, 2009)
Abstract. At malaria high endemic area, oftentimes appear a malaria carrier (without clini-cal symptom) due to antibody parasite existence on blood as caused the frequently of contact human with malaria parasite.To detect prevalence of malaria carrier, it had been conducted a study at Pamotan and Bagolo villages with blood microscopically examination for malaria parasites existences.The study’s results were showing is both villages are malaria high endemic area because is found 3.48% among blood sample is positive parasite Plasmodium falciparum. The citizen in 1-5 year age group and also adult group (> 15 year) with job as housewife and coconut sugar worker are highest risk to malaria attack than the others. Furthermore was suggested, that the highest risk group citizen must be priority in every malaria programs, and also be suggested to conduct periodically survey to find and treat a malaria carrier to prevent ma-laria case appearance and avoid malaria out-breaks.